PENGARUH JARAK ANTAR ELEKTRODA PLAT BESI TERHADAP PRODUKTIVITAS DAN EFISIENSI GENERATOR HHO MENGGUNAKAN METODE ELEKTROLISIS AIR LAUT DENGAN KATALIS KOH - Akhmad Daudi Shabahaini; Mastiadi Tamjidillah (Scientific Journal of Mechanical Engineering Kinematika, 2019)
HHO gas is an alternative energy that can replace fossil energy sources. HHO gas itself can be produced in several ways, one of which uses water electrolysis. Water is given a direct electric charge so that the water molecule (H2O) splits into HHO gas. This study aims to determine the effect of iron plate electrode distance on the productivity and efficiency of HHO generator by varying it from 2 mm, 4 mm and 6 mm, for the water used is the sea water of Teluk Tamiang Village which was dissolved together with KOH of 3,04%. From the experiments carried out the data obtained in the form of voltage, current, time to produce 50 ml of HHO gas, pH of sea water, pH of the solution before and after electrolysis, and temperature after electrolysis. The data is then processed so that it gets the highest productivity at a distance of 2 mm with an average flow rate of 0,89 ml/s and the highest efficiency at a distance of 2 mm with an average of 23,83%. This is because at a distance of 2 mm the electrons move from the cathode electrode to the anode electrode faster and the resulting resistance is smaller, so that the HHO generator produces faster oxyhydrogen bubbles and less power and energy consumption.